Fulminant hepatitis. Presentation of 3 cases and review of the literature (Colombia Medica, 1986)
Three cases of fulminant hepatitis in women are presented, two of which died. In two of them, there was a history of medications. A literature review was done, analyzing the different causes and clinical picture of this form of hepatitis.